Response of morphological, anatomical, and agronomic characteristics of soybean genotypes to Cowpea Mild Mottle Virus - SITI ZUBAIDAH; IMAMA MUJTAHIDA; HERU KUSWANTORO (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Zubaidah S, Mujtahida I, Kuswantoro H. 2023. Response of morphological, anatomical and agronomic characteristics of soybean genotypes to Cowpea Mild Mottle Virus. Biodoversitas 24: 4017-4026. Cowpea Mild Mottle Virus (CpMMV) is a significant disease in soybeans. This disease can cause plant malformations and reduce seed yields. The study used a randomized block design with three replications. Plant materials were five resistant genotypes (MLGG 0006, MLGG 0106, MLGG 0297, MLGG 0315, and MLGG 0599) and five susceptible genotypes (MLGG 0123, MLGG 0379, MLGG 0603, MLGG 0695, and MLGG 0796). The results showed a significant difference between resistant and susceptible genotypes to CpMMV attack. Resistant soybean genotypes had relatively tall stems, many branches, and larger leaf widths. The number of stomata and trichomes of the resistant genotype was less than that of the susceptible genotype. The number of filled pods, the total number of pods per plant, and the number of seeds of the resistant genotype had more numbers than the susceptible genotype. MLGG 0695 was the most responsive genotype because it had a relatively low stem height, few branches, small leaf size, many stomata and trichomes on the leaf surface, the thickest leaf size, and a small number of pods and seeds. The most resistant soybean genotype was MLGG 0297, having a relatively high stem, many branches, large leaf size, few stomata and trichomes on the leaf surface, thin leaf size, and many more pods and seeds. MLGG 0297 can be used as a gene source to develop a superior variety resistant to CpMMV.